The social animal / Elliot Aronson. - Aronson, Elliot. (A Series of books in psychology., 1995)
How are the beliefs and behaviors of people influenced by others? For more than twenty years, Elliot Aronson's The Social Animal has been captivating readers by looking at the answers to this multifaceted question. Presenting the story of modern social psychology as a vivid, engaging narrative, Aronson has provided the most authoritative and accessible introduction to the field available. And by staying close to the real work of social psychologists, he ensures that each new edition incorporates the most important recent research and insights. The result: a classic - venerable yet vibrant. With this new edition, Aronson updates his examination of the patterns and motives of human behavior. Focusing on classic and contemporary studies on conformity, sexual attraction, politics, race relations, advertising, war, and scientific ethics, he incorporates much new information and understanding, including analyses of the Los Angeles riots, U.S. involvement in Somalia, the controversies over false memory and smokers' rights, and other front-page events. The Social Animal captures the creativity of scientific inquiry into human interaction. It draws readers into the excitement of social psychology while clearly explaining its fundamental principles and applications to everyday life.